Pengaruh Pendidikan Kesehatan dengan Media Animasi Terhadap Praktik Menggosok Gigi pada Anak di SDN Margomulyo 1 - Febrianingrum, Bella; Ferianto, Ferianto (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Background: School-age children were considered vulnerable to health problems, especially dental health. In 2018, the prevalence of dental and oral problems in children aged 5–9 years in Indonesia reached 67.3%, in Yogyakarta Special Region (DIY) 65.6%, and in Sleman 42.64%. Brushing teeth was an effort to prevent dental and oral problems in children, so health education through animated media became a promotive strategy to support the Indonesia Free from Caries 2030 program. Objective: To determine the effect of animated media on toothbrushing practices in children at SDN Margomulyo 1. Methods: This study was quantitative research using a one-group pretest-posttest pre-experimental design. It involved 47 students from grades 1 and 2 as samples using total sampling. Toothbrushing practice was measured using observation sheets before and after health education with animated media. Data were analyzed using univariate and bivariate analyses. Bivariate analysis was performed using the Marginal Homogeneity test with The SPSS Program. Results: Before the intervention with animated media, most respondents were in the poor category, with 42 respondents (89.4%), and 5 respondents (10.6%) were in the fair category. After the intervention, 46 respondents (97.9%) had good toothbrushing practices. Statistical analysis using the Marginal Homogeneity test showed a p-value of 0.000 (p<0.05). Conclusion: This study showed that animated media were effective in improving children’s toothbrushing practices and could be utilized in school health promotion.